Impact of impulsivity, perceived social support, and coping on Chinese adolescents' engagement in risky behaviours. - See, Yih Yun. (2010)
A multi-wave longitudinal data was used in current study to test whether coping strategies adoption would mediate the relationship between impulsivity and risky behaviors. Three impulsivity subtraits (attentional/motor/non-planning impulsiveness) proposed by Barratt (1985) were explored in the mediation analysis. Moderation effect of perceived social support on the associations of the impulsivity subtraits and coping strategies adoption were further examined. Results of multilevel modeling indicated that employment of coping strategies mediated the relationship between impulsivity subtraits and risky behaviors. However, perceived social support did not significantly moderate the relationship between impulsivity and use of coping strategies. Main effect of perceived social support on higher proportion of adaptive coping strategies used were found. Limitations and implications of the current study were discussed.